AMT Control Strategy Simulation Study of Electric Bus based on Cruise and Matlab/Simulink - Qin Hongyan; Liu Jingjing; Jiang Fachao; Qiu Bin (Jixie chuandong)
By using the multi-shift transmission system,the drivability and economy of electric bus could be improved,the requirement of motor performance is reduced and the diving range is extended. The AMT control strategy model of electric bus is built,the shifting control strategy is developed and the shifting schedule is optimized. By analyzing the motor characteristics,as well as the clutch performance evaluation in the process of starting and shifting,a control strategy of motor and clutch is developed based on Matlab / Simulink. A simulation model is built based on Cruise and shift schedules based on the principle of best power performance and best economy performance. The simulation result indicated that the control strategy is able to make the motor work in high efficient area and improve the operation efficiency of the motor.